The Future of Medical Devices: Smart Solutions for Healthcare Challenges - odah, Saif hussun; Fadhil, Ghufran Abbas; habo Al_Taie, Ahmad salim; Al-shwekhi, Mohammed Mhmood Lateef; Ali, Lena Asaad (American Journal of Biodiversity, 2025)
Modern medicine faces a range of challenges related to the increasing need for healthcare services. The growing volume of any kind of patient data is another one of the said challenges. One has to consider the rapid growth of technologies, including the development of new effective methods of treatment. All the technology processes conducted in healthcare require proper equipment.The market with medical devices is currently growing faster than any time before. From 2010 to 2019, it grew as much as 38% in terms of revenue. The hardware base also improved, leading to the production of mixed and augmented reality medical devices that started to be adopted in all fields of medicine. This significant extension of resources allows the development of new complex medical devices. These medical devices will be adopted in medicine under the joint name of smart solutions. So the health information technology (HIT) segment boosts the healthcare process the most voracious way. This segment emerged up to 1996 and from this moment the technology has been spreading. In the USA, 19% of hospitals were connected in 2008. HIT is a set of platforms that guaranteed the functioning technology, spreading the useful information across healthcare areas to support the healthcare process. The points like a decrease of government pressure, maturity of the telecommunications market, and social networks may request a revision of the concept of mobile health.